The Organic Foods In The Context Of Halalan Tayyiban - Mohammed Mouaz bin Maulana Abed Ali Hafeji (Penerbit Hellow Pustaka, 2025)
This study aims to explore and establish the relationship, if any, between halalan toyyiban and organic foods, aiming to elucidate the value proposition of halalan-toyyiban foods. Three common characteristics have been identified: quality, safety, and healthiness, which are representative of both halalan-toyyiban and organic foods. This discovery implies a close relationship between these two food classifications. Understanding the distinct criteria used to classify foods as halalan toyyiban or organic, and identifying their shared characteristics, can aid consumers in making informed food choices. Furthermore, the findings of this study could potentially benefit Malaysia in promoting halalan toyyiban and organic food products in the global market by leveraging these commonalities. It's important to note that this study is exploratory and the first of its kind, suggesting the need for further research to deepen understanding and knowledge on this subject. In conclusion, this research seeks to contribute to the discourse on halalan toyyiban and organic foods, exploring synergies between them and paving the way for future studies to expand upon these findings.